SIRT3 inhibitor 3-TYP exacerbates thioacetamide-induced hepatic injury in mice - Shi, Chunxia; Jiao, Fangzhou; Wang, Yao; Chen, Qian; Wang, Luwen; Gong, Zuojiong (Frontiers in Physiology, 2022)
The purpose of the study was to explore the effects of SIRT3 inhibitor 3-TYP on acute liver failure (ALF) in mice and its underlying mechanism. The mice were treated with thioacetamide (TAA, 300 mg/kg) for inducing ALF model. 3-TYP (50 mg/kg) was administered 2h prior to TAA. The liver histological changes were measured by HE staining. Blood samples were collected for analysis of alanine aminotransferase (ALT) and aspartate aminotransferase (AST). MDA and GSH were used to evaluate the oxidative stress of liver. The expression levels of inflammatory cytokines (TNF-α and IL-1β) were measured by ELISA and Western blotting. The cell type expression of IL-1β in liver tissue was detected by immunofluorescent staining. The expression of SIRT3, MnSOD, ALDH2, MAPK, NF-κB, Nrf2/HO-1, p-elF2α/CHOP, and cleaved caspase 3 was determined by Western blotting. TUNEL staining was performed to detect the apoptosis cells of liver tissues. 3-TYP exacerbated the liver injury of ALF mice. 3-TYP increase the inflammatory responses and activation of MAPK and NF-κB pathways. In addition, 3-TYP administration enhanced the damage of oxidative stress, endoplasmic reticulum stress, and promoted hepatocyte apoptosis in ALF mice. 3-TYP exacerbates thioacetamide-induced hepatic injury in mice. Activation of SIRT3 could be a promising target for the treatment of ALF.